Il mago Sabbiolino e la Contadina: anaffettività e indifferenza nella storia della psichiatria* - Lucarini, Emauela; Trevisan, Niccolò (Il sogno della farfalla, 2017)
By rereading The Sandman (Der Sandmann), the well-known short story by E. T. A. Hoffman, the authors outline the difference between the terms the lack of affectivity and indifference. This difference, which was conceptualized by Massimo Fagioli, becomes extremely relevant within both his theoretical work (Human Birth Theory) and therapeutic practice (Analisi collettiva) in the light of recent outcomes on the activation of human brain at birth. Differently from such authors who made history in psychiatry as Bleuler, Jaspers and Freud, Fagioli defined the lack of affectivity on pulsional basis as the loss of affectivity due to the annulment pulsion. Whatever remains of the original vitality in patients’ psychic reality may represent the key to read different clinical pictures – schizophrenia, non-affective psychosis, and depression – uniformly. If it is true that the lack of affectivity is peculiar to the mentally ill, indifference, with which it has been confused, is an affection of sane people and can be expressed and found in writing, arts, and dream interpretation.